Reasoning skills among students: a meta-analysis - Johnny, Jacinta (2015)
Many countries have undergone a paradigm shift in their approach of teaching, learning and assessment where emphasis is heavily placed on thinking skills. This skill is indeed a vital requirement in developing twenty-first century skills among students as there is a need for high levels of thinking, reasoning and collaborating in today’s era. In the Malaysian context, there is a current need in elevating reasoning skills among high achievers as the Ministry of Education has realized that high achievers have not been performing excellently in global assessments, specifically. Therefore, this conceptual paper aims at identifying the components of reasoning skills that high achievers face difficulties in when learning Mathematics. From the meta-analysis conducted, two major components of reasoning skills were identified; knowledge reasoning and systemic thinking. Based on these findings from literature, these two components can be used as a learning framework to elevate students reasoning skills.